2016
DOI: 10.1016/j.cdtm.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of hypertensive intracerebral hemorrhage: A technical review

Abstract: Hypertensive intracerebral hemorrhage (ICH) is still a highlighting global issue. Endoscopic evacuation as a minimally invasive treatment became an alternative other than conventional craniotomy and catheter drainage for ICH. However, there is no unified indication or standardized procedure on endoscopic treatment of ICH. Here we explored the literature and gathered information from different studies, to review the background, technical points, and existing problems of endoscopic treatment for ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Compared with craniotomy, endoscopic evacuation of ICH has several advantages, such as minimal invasive procedure, fewer complications, higher magnification, shorter operation period, and better prognosis 5,9,10 . It has a broad prospect in the surgical treatment of HICH 11 . In the last two decades, the endoscopic evacuation rate of intracerebral hematomas has been rather low, because the narrow hematoma cavity can obstruct the endoscopic view 6,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with craniotomy, endoscopic evacuation of ICH has several advantages, such as minimal invasive procedure, fewer complications, higher magnification, shorter operation period, and better prognosis 5,9,10 . It has a broad prospect in the surgical treatment of HICH 11 . In the last two decades, the endoscopic evacuation rate of intracerebral hematomas has been rather low, because the narrow hematoma cavity can obstruct the endoscopic view 6,12 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 , 13 , 20 ] As a promising type of MIS, the effect of endoscopic surgery in ICH appears favorable in some studies. [ 7 , 15 , 24 - 26 ] Since it is less invasive, endoscopic surgery has been considered as the most convenient treatment for ICH,[ 27 ] and its use is currently being validated in the INVEST trial. [ 4 ] Results of recent studies support the use of endoscopic surgery,[ 7 , 11 , 15 , 26 ] but, to the best of our knowledge, to date, there are no reports focusing on elderly patients, especially comparing the difference between “early” and “late” elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…The neuroendoscopy-based minimally invasive technologies applied to treat ICH are becoming increasingly mature. Some studies [ 23 , 24 , 25 ] have found that neuroendoscopic minimally invasive surgery for hematoma removal has the advantages of less trauma, shorter operation time, less intraoperative blood loss, and higher hematoma clearance rate. However, the MISTIE II and III studies [ 8 , 9 ] found that minimally invasive surgery did not significantly improve neurological function outcomes.…”
Section: Discussionmentioning
confidence: 99%